Ultrafast hot electron dynamics in plasmonic nanostructures: experiments, modelling, design - Schirato Andrea; Maiuri Margherita; Cerullo Giulio; Della Valle Giuseppe (Nanophotonics)
Metallic nanostructures exhibit localized surface plasmons (LSPs), which offer unprecedented opportunities for advanced photonic materials and devices. Following resonant photoexcitation, LSPs quickly dephase, giving rise to a distribution of energetic ‘hot’ electrons in the metal. These out-of-equilibrium carriers undergo ultrafast internal relaxation processes, nowadays pivotal in a variety of applications, from photodetection and sensing to the driving of photochemical reactions and ultrafast all-optical modulation of light. Despite the intense research activity, exploitation of hot carriers for real-world nanophotonic devices remains extremely challenging. This is due to the complexity inherent to hot carrier relaxation phenomena at the nanoscale, involving short-lived out-of-equilibrium electronic states over a very broad range of energies, in interaction with thermal electronic and phononic baths. These issues call for a comprehensive understanding of ultrafast hot electron dynamics in plasmonic nanostructures. This paper aims to review our contribution to the field: starting from the fundamental physics of plasmonic nanostructures, we first describe the experimental techniques used to probe hot electrons; we then introduce a numerical model of ultrafast nanoscale relaxation processes, and present examples in which experiments and modelling are combined, with the aim of designing novel optical functionalities enabled by ultrafast hot-electron dynamics.